STUDY ON THE EFFECTIVENESS OF PRE-HAVEST ACID SALICYLIC SPRAYING ON THE RESISTANCE TO COLD INJURY OF CAT CHU MANGO (Mangifera indica L.) DURING STORAGE - Bui Thi My Hong; Nguyen Thanh Tung; Nguyen Hoang Minh; Pham Hieu Kien; Lam Cao Ngan Vy (HUIT Journal of Science, 2024)
The study was conducted to evaluate the quality changes of Cat Chu mango under conditions of acid salicylic spraying combined with storage temperatures that cause cold injury. The research findings indicate that the optimal post-harvest preservation approach for Cat Chu mangoes involved harvesting them at 90 days of age, with a pre-harvest treatment of acid salicylic at a concentration of 1 mM, followed by storage at low temperatures (around 8 °C). Employing this method led to significantly reduced fruit weight loss, extending the storage time to approximately 5 weeks 5 days while retaining the firmness of the fruit, as well as the levels of total soluble solids, vitamin C content, and total sugar content. Additionally, the mangoes exhibited a high value of lightness on both the skin and flesh. These results provide a valuable foundation for further research on preservation methods and serve as a reference guide for gardeners and food processing enterprises seeking to preserve mangoes after harvest.